Further properties on strongly generalized star semi- continuous mappings - EL-Maghrabi, A.I.; AL-Ahmadi, S.S. (Journal of Global Research in Mathematical Archives(JGRMA), 2013)
The aim of this paper is to introduce and study the class of strongly generalized star semi â€“ closed sets which is weaker than semi-Â closed sets (Crossly and Hildebrand , 1971) and stronger than both Â strongly generalized semi-closed sets (El-Maghrabi and Nasef ,2008) and semi generalized-closed sets (Bhattacharya and Lahiri,1987). Also, through this paper some concepts such as: strongly generalized star semi â€“continuous, strongly generalized star semi â€“closed and strongly generalized star semi â€“homeomorphism maps are discussed and investigated via a strongly generalized star semi â€“closed set. Â (1991) AMS Math. Subject Classification: 54 A05; 54 D10 Â Keywords and Phrases: strongly generalized star semi â€“closed sets, strongly generalized star semi â€“ continuous, strongly generalized star semi â€“irresolute, strongly generalized star semi- closed and strongly generalized star semi â€“ homeomorphism mappings